2017
DOI: 10.1038/npp.2017.162
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Endocannabinoid Signaling and Cannabinoids into the Biology and Treatment of Posttraumatic Stress Disorder

Abstract: Exposure to stress is an undeniable, but in most cases surmountable, part of life. However, in certain individuals, exposure to severe or cumulative stressors can lead to an array of pathological conditions including posttraumatic stress disorder (PTSD), characterized by debilitating trauma-related intrusive thoughts, avoidance behaviors, hyperarousal, as well as depressed mood and anxiety. In the context of the rapidly changing political and legal landscape surrounding use of cannabis products in the USA, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
131
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 362 publications
(470 reference statements)
11
131
0
8
Order By: Relevance
“…Cannabis, a psychoactive substance, is demonstrated to have anti‐inflammatory properties and might be beneficial in the treatment of PTSD . The endocannabinoid system is shown to be involved in multiple aspects of the pathophysiology of PTSD, including inflammatory processes, and in line with this, several uncontrolled or small studies have reported the potential usefulness of cannabis (including whole plant marijuana and related cannabinoids) in the treatment of this disorder, particularly for the domains of sleep and nightmares . At present, however, a balanced view would be that obvious risks of cannabis, such as psychosis and substance misuse, outweigh unestablished benefits for PTSD …”
Section: Potential Anti‐inflammatory Treatment Strategiesmentioning
confidence: 99%
“…Cannabis, a psychoactive substance, is demonstrated to have anti‐inflammatory properties and might be beneficial in the treatment of PTSD . The endocannabinoid system is shown to be involved in multiple aspects of the pathophysiology of PTSD, including inflammatory processes, and in line with this, several uncontrolled or small studies have reported the potential usefulness of cannabis (including whole plant marijuana and related cannabinoids) in the treatment of this disorder, particularly for the domains of sleep and nightmares . At present, however, a balanced view would be that obvious risks of cannabis, such as psychosis and substance misuse, outweigh unestablished benefits for PTSD …”
Section: Potential Anti‐inflammatory Treatment Strategiesmentioning
confidence: 99%
“…As mentioned, catecholamines are compounds produced by the adrenal gland to serve as either neurotransmitters (i.e., dopamine, epinephrine, norepinephrine) for the facilitation of neuronal communication, or as hormones, which regulate physiological functions such as heart rate and blood pressure (Langer, ; Smith & Winkler, ). With regard to pain modulation, fight‐or‐flight responses signal for the release of endocannabinoid‐mediated analgesics, which function to reduce the experience of pain without the immobilizing side effects of opioid analgesics (Dasilva et al, ; Nuseir et al, ; for a review, see Hill, Yehuda, & Patel, ; Hillard, ; Lanius et al, ). These physiological alterations culminate in an active defensive response in animals and humans alike and are coordinated principally by the periaqueductal gray of the midbrain (De Oca et al, ; for a review, see Carrive, ) (Figure ).…”
Section: Fight‐or‐flightmentioning
confidence: 99%
“…Moreover, elucidating conserved molecular mechanisms linking stress to affective psychopathology could reveal novel therapeutic approaches to mitigate the adverse effects of stress on mental health. Although identification of a number of stress-regulatory neuromodulatory signaling systems has revealed potentially novel therapeutic targets for affective disorders, endogenous cannabinoid (eCB) signaling represents a leading drug-development candidate (2017; Hill et al, 2018;Hill and Patel, 2013;Lowe et al, 2018;Patel et al, 2017). eCB signaling systems have been heavily implicated in stress-response physiology and pharmacological augmentation of eCB signaling has been suggested to represent a novel approach for the treatment of stress and trauma-related psychiatric disorders Patel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%